2017
DOI: 10.1016/j.chaos.2017.10.036
|View full text |Cite
|
Sign up to set email alerts
|

Statistical properties of user activity fluctuations in virtual worlds

Abstract: User activity fluctuations reflect the performance of online society. We investigate the statistical properties of 1-min user activity time series of simultaneously online users inhabited in 95 independent virtual worlds. The number of online users exhibits clear intraday and weekly patterns due to human's circadian rhythms and week cycles. Statistical analysis shows that the distribution of absolute activity fluctuations has a power-law tail for 44 virtual worlds with an average tail exponent close to 2.15. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 59 publications
2
8
0
Order By: Relevance
“…Further, the same intraday patterns of standard deviation on working and rest days shows that the variability of days is not related to work or rest, and that it is only related to circadian cycles. Weekly and circadian cycles have been reported by many studies on human behaviors such as web browsing behavior [35], activity in the virtual world [36], and calling activity [29,43]. The intraday patterns in call frequency observed in the present study were similar with those reported in these studies; however, the intraday patterns of average call duration were quite different.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Further, the same intraday patterns of standard deviation on working and rest days shows that the variability of days is not related to work or rest, and that it is only related to circadian cycles. Weekly and circadian cycles have been reported by many studies on human behaviors such as web browsing behavior [35], activity in the virtual world [36], and calling activity [29,43]. The intraday patterns in call frequency observed in the present study were similar with those reported in these studies; however, the intraday patterns of average call duration were quite different.…”
Section: Discussionsupporting
confidence: 86%
“…Studies on dynamics of behaviors such as calling [7,[25][26][27][28][29] and sending short messages [30,31] have revealed that the inter-event time (interval between two activities) exhibits a nonpoisson distribution, which is consistent with the findings of studies on other human behaviors such as email communication [32][33][34] and online activities [35][36][37][38]. There are three popular mechanisms used to explain the non-poisson distribution of inter-event time; decisionbased queuing process [32], adaptive interests [39], and poisson processes modulated by circadian and weekly cycles [33,34].…”
Section: Introductionsupporting
confidence: 79%
See 3 more Smart Citations